Foreign experience in legal regulation of fraud investigation - Yefimov, Mykola; Pavlova, Natalia; Fedchenko, Volodymyr; Pletenets , Viktor; Kryvopusk, Oleksandr (Journal of the University of Zulia, 2022)
The purpose of the research. The purpose of the article is to clarify foreign experience in legal regulation of fraud investigation. Main content. Considered are methods of detecting abuses performed by personnel at foreign enterprises and methods of combating such abuses. Methodology: Review of materials and methods on the basis of analysis of foreign experience concerning legal regulation of fraud investigation. Conclusions. It has been observed that despite legislative and regulatory documents, fraud and other types of crimes committed by employees of various branches are a widespread problem both in Ukraine and abroad. Highlighted the main areas of economic activity where fraud losses account for the largest amounts.